Profil Histopatologi Kerapu Tikus (Cromileptes altivelis) yang Distimulasi Jintan Hitam (Nigella sativa) dan Diinfeksi Viral Nervous Necrosis (VNN) - Septi Diana Sari; Wardiyato Wardiyato; Agus Setyawan (AQUASAINS, 2014)
Black cumin (Nigella sativa) has been used as an immunostimulant in humpback grouper (Cromileptes altivelis) was infected with Viral Nervous Necrosis (VNN). The addition of 7,5% black cumin in fish feed showed to increase innate immune responsee of humpback grouper. However, then was unknown histopathology effect forward black cumin administration in fish. This research purpose was to know  profile of histopathological humpback grouper stimulated black cumin and infected VNN. Fish was organized in five tanks based on treatment i.e control, VNN infected fish, and VNN infected fish with additional 2,5 %, 5 %, and 7,5 % black cumin in fish feed. Then was five organs i.e brain, eyes, kidney, liver, and gills, that observed each fish sample. Result of this research showed that the addition of black cumin, was not affect histopathology profile in humpback grouper that infected with VNN.